PSYCHOPHYSIOLOGICAL CHARACTERISTICS OF CYBERSPORTSMEN DURING INTENSE GAME ACTIVITY - Karvounis Yu.A.; Karvounis N.A.; Kalinnikova Yu.G; Kapilevich L.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to conduct a comparative analysis of the psychophysiological characteristics of cybersportsmen and unprepared persons during intense gaming activity. Methods and structure of the study. A comparative analysis of the psychophysiological characteristics of e-sportsmen and unprepared persons during intense gaming activity was carried out. In total, 40 athletes took part in the work, 20 of them are cybersportsmen and 20 athletes of various sports, who are students of the Faculty of Physical Education of the National Research Tomsk State University. The study was aimed at the primary assessment of the stress resistance of athletes and the specifics of their reactions in order to predict and further prevent the "tilt effect". Results and conclusions. According to the psychophysiological study, cybersportsmen showed a low level of anxiety and lack of discomfort, which is explained by their presence in their own environment, while beginners were partially unstable and felt anxiety and discomfort. According to the test for noise immunity, a fairly high level of the average reaction time of cybersportsmen was established, but a large number of errors were also revealed, primarily errors of lead. The inclusion of psychological practices in the training regimen will also reduce the level of stress among esports athletes and will allow developing individual methods for getting out of the “tilt effect” state for each athlete.